Viewers' perception towards message advertisement that provided by TV3 / Nur Shazwani Abd Rahman (Faculty of Business Management, 2007)
This research was conducted for the purposed of "Viewers' perception towards message advertisement that provided by TV3. The main objective of this research was to identify viewers' perception towards message advertisement that has advertised on TV3. This will provide information about viewers' awareness of an advertisement. Beside that, the purpose of this research is to examine viewers' response from the message advertisement that provided by TV3. This will provide information about persuasion message can influence viewers' response. The respondent of this study was TV3's viewers areas Klang Valley who also known as our customer. The sampling size is 50 respondents and this research was conducted by using non-probability sampling. The sampling method is convenience sampling. The conclusion of this study was the outcome from the survey analysis and findings. Through the research, it shows that the level of viewers' perception is high towards message advertisement on TV3. Therefore, effectiveness message can influence viewers' perception and the objective of this study has been met. Based on the findings, some recommendations have been suggested in order to help increase viewers' perception.